Analysis on Influence Factors of Roadway Instability in High-Stress, Steeply Inclined Extra-Thick Coal Seam - Hai Rong; Liting Pan; Xiaoyan Li; Ming Wang; Zeliang Qu; Mengsheng Lu; Kaipeng Guo (Advances in Civil Engineering)
In order to solve the problem of roadway support safety in coal mining under high stress conditions and to improve safe and efficient production in coal mines, the control countermeasures of the surrounding rock stability and the optimization scheme of support are put forward and the model and numerical simulation of roadway bolt support system are established. Based on bolt support theory and instability mechanism of the coal rock dynamic system, this paper puts forward the evaluation of support effect and the optimization parameters of bolt support, and the scheme of mine pressure monitoring and the corresponding support optimization system are established. The roof fall accident and the bolt and cable of support have been broken in the Wudong coal mine, the phenomenon of bolt pulling out in the roadway. The causes of roof fall are analyzed and the solutions are put forth, judging the influence of different factors on roadway support. In view of the roof fall accident in the North Lane of the east wing of the +575 level 43 #coal seam in the north mining area of the Wudong coal mine, the cause analysis and support suggestions are made. And, according to the performance of the bolting material and anchoring agent, the laboratory theoretical research was carried out. Through the experiment, it is concluded that the FRP bolt with a diameter not less than 27 mm is the first choice for the side support of the working face in the mining roadway, then ribbed steel bolt with a diameter not less than 20 mm for the nonworking face, and the length of the anchor rod not less than the range of the loose circle. Therefore, full-length anchoring should be carried out in roadway support, the anchorage length of the anchor cable should be increased, and the integrity of the roof should be improved, so as to reduce the amount of roadway roof separation and improve the support effect.